Legalidade Tributária e Reserva de Lei no Estado Social (De Legibus - Law Journal, 2022)
The fair distribution of public burdens in the modern welfare state determines the distribution of the tax sacrifice among all citizens, without always burdening the same taxpayers with the part of the taxes that others do not pay. Rethinking the role of the State and equating the action of the Tax Administration calls for reflection on the reserve of law that is compatible with the definition of a margin of appreciation and proof of the facts and of interpretation and decision of the Tax Administration, with no margin of tolerance for the tax evasion.